Variations in the branching pattern of the internal iliac artery and its implications in trauma and surgery – a South Indian cadaveric study - Satheesha Nayak Badagabettu; Ashwini Aithal Padur; Surekha Devadasa Shetty (Jornal Vascular Brasileiro)
ABSTRACT Background The internal iliac artery (IIA) frequently shows variations in its branching pattern. Knowledge of its variations is helpful during gynecological and orthopedic surgical procedures. Objectives To observe the branching pattern of IIA in the human pelvises and discuss its clinical implications. Methods The study was conducted on 80 male hemipelvises (40 left halves and 40 right halves). The pelvic halves were obtained by making mid-line saw cuts through formalin embalmed adult human cadavers aged approximately 50-80 years. The IIA were dissected and cleaned. Variations of the internal iliac artery and its branches were noted. Relevant photographs were taken. Results were expressed as percentages. Results Variations in the branching pattern were observed in 49 (61%) hemipelvises (right: 21, left: 28). Variations were more common (48%) in the branching pattern of the anterior division of IIA than the posterior division (20%). Variations of the main trunk were observed in 29% of cases. In 3% of cases, the IIA did not divide into two divisions. Among the individual branches, the iliolumbar artery showed variations in 29% of cases and the obturator artery in 25%. A common trunk of the internal pudendal and middle rectal arteries was found in 24% of cases and variations of the inferior gluteal artery were seen in 18% of cases. Conclusions The study showed a high rate of occurrence of variant IIA branching patterns. Understanding the anatomical variations of the IIA and its branches is essential to minimize intraoperative blood loss and other complications during pelvic surgeries.